Bilirubin is inversely related to diabetic peripheral neuropathy assessed by sural nerve conduction study. Issue 11 (20th May 2021) - Abe, Kentaro; Maeda, Yasutaka; Matsuzaki, Chitose; Yokomizo, Hisashi; Inoue, Tomoaki; Sonoda, Noriyuki; Ogawa, Yoshihiro; Inoguchi, Toyoshi
Abstract: Aims/Introduction: Diagnosis of diabetic peripheral neuropathy (DPN) depends on subjective findings, certain investigations for DPN risks have not been performed enough. Bilirubin protects against vascular complications by reducing oxidative stress in diabetes, but is not fully tested for DPN. This study aimed to evaluate sural nerve conduction impairments (SNCI) as an objective DPN marker and the contribution of bilirubin to SNCI. Materials and methods: Using DPN‐Check ®, SNCI was defined as a decline of amplitude potential or conduction velocity below the normal limit in 150 inpatients with diabetes. The correlations between SNCI and conventional DPN diagnosis criteria, the incidence of diabetic retinopathy/nephropathy, biomarkers for atherosclerosis, cardiac function by ultrasonic cardiogram, and bilirubin were statistically tested, followed by the comparison of logistic regression models for SNCI to find confounders with bilirubin. Results: The incidence of SNCI was 72.0%. The sensitivity and specificity of SNCI for DPN prediagnosis by simplified criteria were 54.6 and 90.5%, respectively, and similarly corresponded with diabetic retinopathy and nephropathy (sensitivity 57.4 and 50.0%, respectively). SNCI significantly related to diabetes duration, declined estimated glomerular filtration rate, albuminuria and total bilirubin. SNCI incidence was attenuated in the higher bilirubin tertiles (89.8/65.3/54.8%, P  < 0.001). Bilirubin was an independent inverse risk factor for SNCI, even after adjustment by known risk factors for DPN and markers for microvascular complications. Conclusions: SNCI is a comprehensive marker for diabetic complications. We first showed the independent inverse relationship between bilirubin and SNCI through the independent pathway with other complications, provably reducing oxidative stress, as previously reported. Abstract : Sural nerve conduction impairments guaranteed the reasonable agreements with not only subjective diabetic peripheral neuropathy diagnosis criteria, but also other diabetic complications. We confirmed older age, longer diabetes duration, surrogate markers for both micro‐ and macrovascular complications, and total bilirubin as risk factors for diabetic peripheral neuropathy. Furthermore, we first demonstrated the independent inverse relationship between bilirubin and sural nerve conduction impairments. These results provide sural nerve conduction impairments assessment by DPN‐Check ® as a comprehensive marker for diabetic complications in routine medical care for diabetes.